Species Diversity and Species Association of Butterflies (Lepidoptera) in the Riparian Zone of Paneki River, Pombewe Village, Sigi Biromaru District. - Ramadhana, Fauziah; Ihsan, Moh; Ningsih, Sri; Rukmi, Rukmi; Sustri, Sustri (Universitas Andi Djemma Palopo, 2025)
Butterflies play an important role in the riparian ecosystem, influencing the survival of flowering plants along riverbanks. The interactions among butterfly species within an ecosystem are referred to as species associations. These associations indicate complex relationships—both positive and negative—between butterfly species. This study aims to analyze species associations among butterflies (Lepidoptera) in the riparian area of the Paneki River, located in Pombewe Village, Sigi Biromaru District. Data were collected using the transect method and direct observations conducted from morning to afternoon. The results showed a total of 31 butterfly species, represented by 62 individuals. The diversity index and species richness index recorded in the Paneki River riparian area were 3.25 and 3.43, respectively. Meanwhile, the evenness index was 0.94. These three indices suggest that the riparian habitat of the Paneki River supports a high, balanced, and stable diversity of butterfly species.Based on the analysis of species associations in the riparian habitat, 26 butterfly species exhibited associative interactions, forming a total of 296 association links. In contrast, 5 species did not show any associations with other species. The degree of association varied among species, with some exhibiting a high number of associations and others showing fewer.